Nonuniform Ionic and Electronic Transport of Ceramic and Polymer/Ceramic Hybrid Electrolyte by Nanometer‐Scale Operando Imaging for Solid‐State Battery. Issue 21 (20th April 2020) - Jiang, Chun‐Sheng; Dunlap, Nathan; Li, Yejing; Guthrey, Harvey; Liu, Ping; Lee, Se‐Hee; Al‐Jassim, Mowafak M.
Abstract: Replacing the liquid electrolyte in lithium batteries with solid‐state ion conductor is promising for next‐generation energy storage that is safe and has high energy density. Here, nanometer‐resolution ionic and electronic transport imaging of Li3 PS4 (LPS), a solid‐state electrolyte (SSE), is reported. This nm resolution is achieved by using a logarithm‐scale current amplifier that enhances the current sensitivity to the fA range. Large fluctuations of ion current—one to two orders of magnitude on the LPS and on the LPS region of a polymer/LPS bulk hybrid SSE—that must be mitigated to eliminate Li dendrite formation and growth, are found. This ion current fluctuation is understood in terms of highly anisotropic transport kinetic barriers along the different crystalline axes due to different grain orientations in the polycrystalline and glass ceramic materials. The results on the bulk hybrid SSE show a sharp transition of ionic and electronic transport at the LPS/polymer boundary and decreases in average ionic current with decreasing polyimine particle size and with extensive cycling. The results elucidate the mechanism of polyimine extension into interparticles to prevent Li dendrite growth. This work opens up novel characterization of charge transport, which relates to Li plating and stripping for solid‐state‐batteries. Abstract : Nanometer resolution ionic and electronic transport imaging is achieved based on atomic force microscopy by using a logarithm‐scale current amplifier. Large fluctuations of ion current—one to two orders of magnitude on the LPS and on the Li3 PS4 (LPS) region of a polymer/LPS bulk hybrid solid‐state electrolyte—that must be mitigated to eliminate Li dendrite formation and growth in solid‐state batteries, are found.